Optical Properties for Thin Film of Coumarin 334 Organic Laser Dye doped with PVA Polymer and Al2O3 Nanoparticles (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background:In this work, the optical properties for thin film of Coumarin 334 organic laser dye doped with PVA polymer and AL2O3 nanoparticles are determined at different concentrations, dissolved in ethanol solvent.Methods:Solutions at concentration (10-4 M) from coumarin (334) dye  in ethanol solvent at Different concentrations from dye (1, 3, 5, and 7)  ×10-5 M  were  prepared.Results:The AFM measurements show that the  grain size, root mean  square and roughness belong to the surface of the thin films rises with thickness rise for thin films  .  It has also increased the absorbance due to the increase in concentration.Conclusion:By using Gaussian beam from CW pulsed laser at 457 nm, we used Z-scan to study the nonlinear optical properties. The nonlinearity of thin film highly excels the pure dye solutions.